Efektivitas Strategi Contextual Teaching and Learning dalam Pembelajaran Menulis Paragraf Narasi pada Siswa Kelas VII SMP Negeri 32 OKU - Emilia Contessa; Lasmiatun Lasmiatun; Ridho Andi Sucipto (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2023)
The aim of the study was to describe the ability of class VII students of SMP Negeri 32 OKU in writing narrative paragraphs before and after using the Contextual Teaching and Learning strategy, to describe the effectiveness of the Contextual Teaching and Learning strategy in writing narrative paragraphs in class VII SMP Negeri 32 OKU. The method used in this study is an experimental method with a population of 150 students and a sample of 36 students. The data collection technique was writing narrative paragraphs and the data analysis technique used the t-test. The results showed that students' ability to write narrative paragraphs before using the CTL strategy, students who scored between 80 and above did not exist, students who scored between 66-79 there were 15 people (41.67%), students who scored between 56–65 there were 14 people (38.88%), students who scored between 46–55 there were 3 people (8.33%), students who scored between 00–45 were in the failed assessment category, there were 4 people (11, 11%). Then the results of the ability of class VII students of SMP Negeri 32 OKU in writing narrative paragraphs after using the CTL strategy, there were 11 students who scored between 80–100 (30.56%), students who scored between 66–79 there were 24 people (66.67 %), students who scored between 56–65 did not exist, students who scored between 46–55 did not exist, students who scored between 00–45, there was 1 person (2.77%). This increase can be seen from the results of the average pretest score of 57.97 and posttest of 73.97. The results of the